FENOMENA TOP UP DIAMOND GAME FREE FIRE BAGI ANAK YANG BELUM BALIGH DALAM PERSPEKTIF MAQASHID ASY-SYARIAH DI KECAMATAN PONTIANAK BARAT - Muhammad Rezeki Febriyadi; Abu Bakar; Suhardiman Suhardiman (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2024)
This study aims to analyze the phenomenon of Top Up Diamond in the Free Fire game from the Maqashid Asy-Syariah perspective in the West Pontianak District. This research uses a qualitative approach with interview and observation techniques as data collection methods. Respondents in this study are Free Fire game players who do diamond top-ups in the West Pontianak District. The results of the study show that the Top Up Diamond phenomenon can be seen as an act that violates the principles of Maqashid Asy-Syariah, especially the principle of guarding wealth. This research recommends the need for intensive education for users or parents about Maqashid Asy-Syariah so that children are more directed in their lives.